AB0436 Comparison of tofacitinib efficacy in patients with moderate vs severe rheumatoid arthritis: pooled analysis of phase 3 studies. (15th June 2017) - Schwartzman, S; Sunkureddi, P; Takiya, L; Snyder, M; Fan, H; Lukic, T; Roberts, J; Rigby, WFC
Abstract : Background: Tofacitinib is an oral JAK inhibitor for the treatment of RA. Objectives: To evaluate tofacitinib 5 and 10 mg twice daily (BID) efficacy in patients (pts) with moderate vs severe RA. Methods: Tofacitinib 5 and 10 mg BID efficacy data were obtained from 6 randomised double-blind Phase 3 studies of 6–24 months' duration. Tofacitinib was administered as monotherapy (NCT00814307 ORAL Solo; NCT01039688 ORAL Start) or with csDMARDs, mainly MTX (NCT00960440 ORAL Step; NCT00847613 ORAL Scan; NCT00856544 ORAL Sync; NCT00853385 ORAL Standard). Pts receiving MTX monotherapy (ORAL Start), or placebo (±csDMARDs) were combined as a single "placebo" group. Baseline (BL) disease severity was classified as moderate or severe using Disease Activity Score in 28 joints with erythrocyte sedimentation rate (DAS28: moderate 3.2 to ≤5.1; severe >5.1) and Clinical Disease Activity Index (CDAI: moderate 10 to ≤22; severe >22). Month 3 (M3) efficacy outcomes included: pts (%) achieving low disease activity (LDA; DAS28 ≤3.2, CDAI ≤10), remission (DAS28 <2.6, CDAI ≤2.8), HAQ-DI <0.5 (normal physical functioning), HAQ-DI improvement >0.22 and mean change from BL (Δ) in DAS28, CDAI and HAQ-DI. This post hoc analysis had no multiplicity adjustments. Results: Overall, more pts had severe BL disease by DAS28 (91.0%) and CDAI (89.5%). The table shows BL disease characteristics and M3 efficacy outcomes for pts classified by BL DAS28 disease severity; CDAI classification demonstrated similar trends. BL characteristics were balanced between treatment groups in each disease severity category. M3 efficacy was significantly greater with tofacitinib 5 and 10 mg BID vs placebo, regardless of BL disease severity. As expected, larger proportions of tofacitinib-treated pts with moderate vs severe BL RA achieved LDA by either DAS28 (32.3–36.7% vs 13.8–19.1%) or CDAI (49.2–55.0% vs 26.0–31.7%). Similarly, a higher proportion of pts achieved remission in the moderate vs severe BL groups by DAS28 (20.0–22.8% vs 6.2–9.0%) or CDAI (11.5–12.1% vs 5.1–6.7%). A greater proportion of pts achieved HAQ-DI <0.5 with moderate vs severe RA classified by BL DAS28 (45.0–60.6% vs 24.5–30.0%) or BL CDAI (40.8–52.4% vs 24.7–30.4%). Greater improvements from BL in disease activity and HAQ-DI were seen for pts with severe vs moderate RA classified by BL DAS28 (Table), and by BL CDAI (Tofacitinib 5/10 mg BID ΔCDAI: -21.1/-23.0 vs -8.1/-9.4; ΔHAQ DI: -0.5/-0.6 vs -0.3/-0.4). Conclusions: Tofacitinib 5 and 10 mg BID demonstrated efficacy in treating pts with moderate and severe RA with >7 years' mean disease duration. By M3, pts with severe vs moderate BL disease activity had greater improvements in disease activity and physical functioning; higher proportions of pts with moderate vs severe BL disease activity achieved remission, LDA or normal physical functioning. Interpretation of this post hoc analysis may be limited by the smaller sample size of the moderate disease group and the combining of mono- and combination-therapy results. Acknowledgements: This study was sponsored by Pfizer Inc. Editorial support was provided by A Pedder of CMC and funded by Pfizer Inc. Disclosure of Interest: S. Schwartzman Consultant for: Pfizer Inc, P. Sunkureddi Grant/research support from: Pfizer Inc, Consultant for: Pfizer Inc, Speakers bureau: Pfizer Inc, L. Takiya Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, M. Snyder Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, H. Fan Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Lukic Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Roberts Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, W. F. Rigby Grant/research support from: Amgen, Pfizer Inc, Roche, Consultant for: Bristol-Myers Squibb, Eli Lilly, Pfizer Inc, Roche